BIOGRAFI MADALI SYA’BAN SEBAGAI TOKOH TARI DI BENGKULU SELATAN - Cindhy Pospita Wati; Afifah Asriati; Nerosti Nerosti (FBS Universitas Negeri Padang, 2018)
Abstract The research was distributed by Madali Sha'baan as a dance that already work in introducing dance from South Bengkulu. This research aims to disclose and describe the biography in the course of artistic activity as a dance of Sha'baan Madali in South Bengkulu. This type of research is qualitative research with a diakronis approach and method of history (historical). The object of the study is as a character through Madali dance in South Bengkulu. The research instrument was its own researchers and supporting instruments such as assisted with photo camera, digital camera, stationery and audio conversation tool. The type of data in this study is the primary data and secondary data. Engineering data collection done by the study of librarianship, observation/observation, interview and documentation. Processing of data is carried out by means of an interactive analysis. The results showed that the character is a choreographer of Sha'baan Madali acknowledged. Its action in the archives starting from 1994 to the present and has earned an award from the Government of the province of Bengkulu as choreographed dance in 2008. He was born by the family of the artist's background, but with his creativity he is capable of working in the world of dance in South Bengkulu. Dance works that are already created by Madali Sha'baan can be distinguished into two forms of paper, namely: (1) traditional dance. (2) Dance creations. Works on motion of Sha'baan Madali tradition Dance Andun and based on the phenomena of society South Bengkulu. With both categories works Madali Sha'baan have managed to introduce the arts of the South Sumatra especially the art of dance to the public. Keywords: biography, Madali Shya'ban, Character Dance